Self-assembly directed one-step synthesis of [4]radialene on Cu(100) surfaces - Qing Li (Nature Portfolio, 2018)
Radialenes have distinct structural, electronic and chemical properties from other hydrocarbons, but their synthesis remains a challenge. Here, the authors report a copper catalyzed one-step synthetic protocol of [4]radialene via the cyclotetramerization of phenylacetylene molecules upon thermal activation.